A Translation of Cultural Words in Julian Millie’s People’s Religion Book: An Ideological Perspective - Rahmah, Ilma Yullinda; Yahya, Mohammad; Firdhani, Anggi Rizky; Wulansari, Damayanti (Kajian Linguistik dan Sastra, 2025)
This study focuses on translation ideology in rendering cultural words from Sundanese into English in atranslated book by Julian Millie entitled People’s Religion, focusing on Sundanese sermons by theIndonesian preacher AF Ghazali. We investigate how cultural terms are translated and what ideologicalstances are reflected through the strategies used. The analysis employs a qualitative descriptive methodwith data drawn from 70 culturally specific words. The study uses Newmark’s (1988) taxonomy ofcultural categories and integrates translation strategies from multiple theorists to identify patterns.Venuti’s (1995) concept of foreignization and domestication is used as the primary ideologicalframework, supported by Hatim and Mason’s (1997) critical discourse approach to interpret thetranslator’s decisions. Importantly, this study introduces a third category, which is a hybrid ideology, toaccommodate cases where mixed strategies are used, reflecting the translator’s flexible negotiationbetween source and target culture. The findings from 70 data samples reveal that domestication (30 data) is the most dominant ideology, followed by foreignization (25 data), and hybrid ideology (15 data).These results demonstrate that the translator tends to prioritize readability and accessibility for thetarget readers yet also retains some cultural authenticity when deemed necessary. The findings suggestthat translation of cultural words is a deeply ideological process that requires critical strategy selectionto balance cultural authenticity with reader accessibility.